Faunistic and bibliographical inventory of the blackflies (Diptera: Simuliidae) of Morocco - Belqat, Boutaïna; Adler, Peter H.; Crosskey, Roger W. (Zootaxa, 2011)
All published records are provided for the 42 species of black flies known from Morocco, together with appropriate literature references and misidentifications where known. New records of S. lundstromi are presented for the Rif.